(untitled) (Al-Academy, 2016)
The importance of culture moot ( visual ) in the community , serves as the conceptual basis for the technical and aesthetic awareness , as all the fields of art represents a kind of social consciousness can not be separated from the practice of performance and awareness of it. That the link between what you do image that expresses the cognitive aspects and performance , and what is reflected on the receiver by turning the event into a set of symbols and meanings that have a correlation relationship to society , education, and other fields. Therefore must provide " material conditions and psychological " that helps the learner to interact effectively and with the active elements of the learning environment in the classroom and gain experience , knowledge and technical skills , attitudes and values needed by the learner commensurate with his abilities and aptitudes and easiest methods and styles as possible. And must be available to the learner ’s mental and psychological readiness to acquire that information and expertise and skills within its presence in the learning environment include educational content and teacher, a teacher and educational means and techniques to achieve the desired educational goals . The research aims to: - First : Detection of configuration elements in the artwork . Secondly, the design of an educational program for technical configuration elements for the development of technical capacity for secondary school students _ the fourth grade .Third, the effectiveness of the educational program through its application to an experimental sample of secondary school students - fourth grade for the academic year 2012_2013 , and to validate the second goal and put the researcher Cefreeten two assumptions . The research community of the fourth grade students of preparatory secondary school affiliated to the Directorate General of Educational Baghdad Rusafa first . To achieve the goals of research researcher designed an educational program in the technical elements of the configuration with two types of tests of knowledge and skill and to show the results adopted a set of statistical methods : 1 - equation Mann Whitney test : 2 - coefficient of difficulty Difficulty Equation3- coefficient discrimination Discrimination Equation4 - Richardson equation Kiodor -20 Kauder Richardson -20- 5 - reliability coefficient estimate or correction